Pengaruh Penambahan Perasan Paprika Merah (Capsicum annuum) dalam Pakan Terhadap Tingkat Kecerahan Warna Ikan Koi (Cyprinus carpio L.) [The Influence of Additional Red Pepper (Capsicum annuum) Juice in Fish Feed to Koi (Cyprinus Carpio L.) Color Brightness Level] - Wahju Tjahjaningsih; Moch. Amin Alamsjah; Nindya Putriana (Jurnal Ilmiah Perikanan dan Kelautan, 2015)
Abstract Koi fish (Cyprinus carpio L.) is high economical fish and has some type of color and pattern on its body. Koi fish (C. carpio L.) is particularly prone to unstable water quality so the fish with prime condition is very limited. To get the fish with the prime condition required several supporting factors such as the genetic, environment and nutritional feed. In this research the used of red pepper (Capsicum annuum) juice as an additional ingredient in fish feed. The aim of this research is to know about the influence of additional red pepper juice (C. annuum) to the brightness of the color of koi fish (C. carpio L.) and the optimal concentration. There are six treatment used in this research, which are treatment A just given by pelet as a control, B treatment is adding red pepper juice by concentration of 1%, C by concentration of 3% and D by concentration of 5%. E treatment is adding carrot juice by concentrations of 4.5% and F treatment is adding astaxanthin by concentration of 1%. Each treatment given to fish with the level of color brightness that has score 2. The result of color scoring tested by experiment description method that in the end of research on A treatment (control) didn't increase with the same score 2. B treatment (red pepper 1%) increased from score 2 to score 3 started from day 28. C treatment (red pepper 3%) increased from score 2 to score 3 started from day 21. D treatment (red pepper 5%) increased from score 2 to score 4 started from day 21. E treatment (carrot 4,5%) increased from score 2 to score 4 started from day 28. F treatment (astaxanthin 1%) increased from score 2 to score 4 started from day 21.